Quelques remarques sur l’origine des proverbes - Jean-Claude Anscombre (Lexis: Journal in English Lexicology)
This study aims at a thorough examination of the parameters behind the emergence of a given proverb in a given language and at a given time. Proverbs, like lexical items or certain syntactic constructions, are born, develop and eventually disappear. Our reflection will start from the observation that the formulation the origin of proverbs is indeed extremely vague. A proverb is in fact the result of the action of several parameters: a) the sapiential lesson: every proverb rests fundamentally on an implicative pivot of the type ‘if you have P, you have Q’, either to apply it (Like father, like son), or to reject it (A swallow doesn’t make a summer). This sapiential lesson is linked to the culture and beliefs of the community concerned and may not exist in another culture; b) the metaphor used to represent P and Q: it is to be expected, for example, that a culture where the swallow has no relevant place will appeal to another metaphor to represent the sapiential lesson contained in A swallow does not make summer; c) the form of proverbs: studies of sententious forms show that proverbs are generally based on a small number of patterns - around a dozen - which strictly limit variations. These patterns are characteristic of a specific language or group of languages and make it possible to identify proverbs in a given language; d) finally, a significant number of proverbs show rhythmic and / or metrical structures in small numbers. The interesting point is that a sapiential form, even if it doesn’t have such a structure at first, always ends up acquiring one, as we will show with specific examples.